Contributions of the Subregions of the Medial Prefrontal Cortex to Negative Occasion Setting. - MacLeod, Jill E.; Bucci, David J. (Behavioral Neuroscience, 2010)
The medial prefrontal cortex of rats has a role in many aspects of cognitive function, including forms of inhibitory learning. Recent studies suggest that there is heterogeneity in the contributions of the prelimbic (PL) and infralimbic (IL) regions of the medial prefrontal cortex to response inhibition. The present study tested the effects of separate neurotoxic lesions of the PL or IL on a serial feature negative discrimination task (negative occasion setting). Rats received training sessions consisting of 16 trials: on 4 trials in each session, a tone was presented and followed by food reward; on the other 12 trials the tone was preceded by a visual stimulus and not reinforced. The results indicate that PL but not IL is necessary for learning the discrimination. We then tested the effects of these lesions on rats that were first extensively trained in the task. Rats that had been trained for 30 days before receiving PL or IL lesions were still able to perform the task as well as controls after surgery. Thus, PL lesions disrupt acquisition but not performance of a serial feature negative discrimination.